LA INFLUENCIA DE LOS VIDEOJUEGOS EN LA COMUNICACIÓN INTRAFAMILIAR DE LOS ESTUDIANTES DE 15 A 17 AÑOS DE LA UNIDAD EDUCATIVA RENÁN OLMEDO GONZÁLEZ, EL EMPALME. - Zamora Medina, Carlos Enrique (2022)
This research entitled: "the influence of video games on intrafamily communication of students aged 15 to 17 years of the Renán Olmedo González Educational Unit, El Empalme", had as its main objective to identify the influence of video games on intrafamily communication of students. students. It was developed from the qualitative and quantitative paradigm, that through a survey certain issues could be known. Through this research, it was found that in the group of 170 respondents, video games do not influence intra-family communication, this is due to the fact that most of the students do not spend much time using video games. Even so, other points that should be considered important were also identified, one of them refers to the fact that the respondents dedicate a large part of their time to productive things, perhaps because they live in a rural area. At the end of this project, a training plan is suggested, which is made up of topics and workshops, these will help students learn more about video games and communication at home and develop aspects that are a priority in their daily lives. home.